2010
DOI: 10.3109/09537101003777947
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin can stimulate luminol-enhanced chemiluminescence of activated platelets

Abstract: A preliminary investigation was conducted into the influence of aspirin on the luminol-enhanced chemiluminescence of platelets stimulated with platelet-activating factor (PAF). Ten coronary artery disease patients and six volunteers without coronary artery disease were included in the study. All the patients received aspirin (daily dose, 100 mg) for at least 10 days before in vitro experiments. Luminol-enhanced luminescence of platelet-rich plasma samples mixed with a PAF solution was measured. After stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 14 publications
0
3
0
4
Order By: Relevance
“…In our previous study 2 out of 10 CAD patients demonstrated similar ROS generation in response to stimulation with PAF. In the study it has been shown that aspirin can stimulate ROS generation in vitro, and the intake of aspirin by the studied CAD patients was suggested as a possible explanation of observed generation of ROS in two of them [8]. In the current study, patients were also receiving aspirin and its intake can be the reason of increased ROS production 8-10 days after AMI onset.…”
Section: Identification Of Cd45 þ Platelets In Patients With Amimentioning
confidence: 82%
See 1 more Smart Citation
“…In our previous study 2 out of 10 CAD patients demonstrated similar ROS generation in response to stimulation with PAF. In the study it has been shown that aspirin can stimulate ROS generation in vitro, and the intake of aspirin by the studied CAD patients was suggested as a possible explanation of observed generation of ROS in two of them [8]. In the current study, patients were also receiving aspirin and its intake can be the reason of increased ROS production 8-10 days after AMI onset.…”
Section: Identification Of Cd45 þ Platelets In Patients With Amimentioning
confidence: 82%
“…Platelets in some coronary artery disease (CAD) patients are potent ROS producers [8]. However, mere activation of isolated platelets seems not to be enough for ROS generation, since even potent inducers of platelet aggregation such as phorbol ester, calcium ionophore A23187, and thrombin, while causing platelet aggregation do not trigger ROS production, as evaluated from low chemiluminescence in the presence of luminol [9].…”
Section: Introductionmentioning
confidence: 99%
“…УЛХТ измеряли в относительных световых единицах (relative light unit -RLU). Более подробное описание этапов проведения измерения ФАТ-стимулированной УЛХТ опубликовано нами ранее [10,11].…”
Section: материал и методыunclassified
“…Усиленная люминолом хемилюминесценция позволяет оценить образование АФК в тромбоцитах. Вырабатываемые АФК могут выполнять роль вторичных мессенджеров и регулировать функцию тромбоцитов [9,10]. В наших предыдущих работах была продемонстрирована in vitro возможность усиленной люминолом хемилюминесценции тромбоцитов (УЛХТ), Results.…”
Section: Introductionunclassified
See 1 more Smart Citation